Revised physical parameters and study on magnetic activities for the eclipsing binary USNO-B1.0 1387-0467554. Issue 4 (7th April 2023) - Wang, Jianhua; Gu, Shenghong; Wang, Xiaobin; Yeung, Bill; Ng, Eric; Yu, Kamfung; Sun, Leilei; Xiang, Yue; Cao, Dongtao; Bai, Jinming; Fan, Yufeng; Xu, Fukun; et al.
ABSTRACT: We present optimized physical parameters of the active eclipsing binary system USNO-B1.0 1387-0467554 discovered recently in Yunnan–Hong Kong wide-field photometric (YNHK) survey, based on the analysis of its two colour light curves and low resolution spectra obtained at Yunnan Observatories, China. Its spot distributions are derived by means of the Wilson–Devinney code, using photometric data of the YNHK survey from 2016 to 2021. There exist active longitude belts for the spot activities on the primary star, for which the effect of tidal force seems dominant comparing with the one of common magnetic field of the binary system. We have investigated its chromospheric activities through the indicators including Hα, Hβ, CaII H&K, and HeI D3 lines covered by the low resolution spectroscopic observations. There are obvious spatial correlations between the magnetic activities in its photosphere and chromosphere. The E H α / E H β values suggest that both plages and prominences led to the emissions seen in the Balmer lines at most phases. A prominence structure appeared around the phase of 0.8 on 2018 October 25 and evolved in November and December, 2018. The spectra demonstrate that there were frequent flare events in the system. Moreover, the decay part of a white-light flare event was hunted by the YNHK survey on 2021 October 26.